Threat of New Entrants and Competitive Rivalry on Indonesian SMEs’ Performance: The Mediating Role of Market Access - Faisal Hamdi; Silvana Syah; Ruland Willy Jack Sumampouw (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study aims to examine both the direct and indirect effects of external competitive pressures—specifically the threat of new entrants and competitive rivalry—on the performance of Indonesian SMEs. Additionally, it investigates the mediating role of market access.Method: A quantitative approach was employed, utilizing secondary survey-based data from 1,871 Indonesian SMEs recorded in the national credit guarantee database of a state-owned guarantee institution. These SMEs represent diverse sectors and regions across Indonesia. Structural equation modeling (SEM) was used to examine both direct and indirect effects, with particular emphasis on the mediating role of market access.Result: The findings confirm that both the threat of new entrants and competitive rivalry have a significant positive impact on SME performance. Market access also demonstrates a significant positive effect on performance and mediates the relationship between external pressures and enhanced SME performance. This underscores market access as a strategic mechanism that transforms competitive challenges into opportunities for SMEs.Practical Implications for Economic Growth and Development: The results suggest that SMEs and policymakers should leverage external competitive pressures to enhance market access components, such as networks, logistics, and digital platforms. Targeted interventions aimed at reducing logistical barriers and improving digital infrastructure can empower SMEs to convert competition into sustainable growth, thus contributing to broader economic development.Originality/Value: This study extends Porter’s Five Forces framework to the context of Indonesian SMEs and confirms the pivotal role of market access as a mediator.